Clinically-useful serum biomarkers for diagnosis and prognosis of sarcoidosis - Ramos Casals, Manuel (2019)
Introduction: Sarcoidosis is a complex systemic disease with a silent, long-term evolution, and a heterogeneous clinical presentation. The diagnostic approach is complex with no single diagnostic test that may confirm the disease. Areas covered: A large list of serum biomarkers has been tested during the last 40 years. In this review, we analyse the potential usefulness in the diagnosis and prognosis of sarcoidosis of serum biomarkers classified according to their corresponding cellular source. Expert commentary: Diagnosis of sarcoidosis must always be approached as a multistep process based on a case-by-case integration of clinical, radiological, histological and serological data, none of which being pathognomonic. We found sIL-2R, CRP, SAA and chitotriosidase to be the best markers to confirm sarcoidosis (highest sensitivity), while ACE, gammaglobulins and lysozyme may be more useful for discarding sarcoidosis (highest specificity), taking into account that with the use of a higher cut-off we can increase specificity and with a lower cut-off we can increase sensitivity. Other biomarkers (TNF-a and CCL18) could help to identify patients with an enhanced risk of developing pulmonary ﬁbrosis or progressive disease. The future scenario of the serological diagnostic approach of sarcoidosis will be the use of multi-assays including biomarkers from different cellular sources.